THE INFLUENCE OF SELF-CONCEPT ON THE STUDENTS’ ACHIEVEMENT MOTIVATION IN 4TH GRADE SDN CITOREK - Oktaviani, Anna Maria; Makrum, Arifin; Nurhasanah, Nina; Sarivah, Iva (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
AbstractThis research aims to determine the significant effect of self-concept on the achievement motivation of 4th grade students at SDN Citorek in 2022 of Cluster 5. The research method used is a survey method with path analysis techniques. This research used questionnaires or statements as data collection techniques to obtain data about the effect of self-concept (X) on achievement motivation (Y) using the Likert scale. The data analysis in this research is descriptive statistical analysis and inferential statistical analysis. The results of the second hypothesis testing can be concluded that self-concept has directly affected achievement motivation with a correlation coefficient score of 0.457 and a path coefficient score of 0.357, which means that self-concept can directly affect achievement motivation.Keywords: Social Science; Self-concept; Achievement Motivation